Atomic structure and periodicity - Barrett, Jack. (Wiley-Interscience, 2002)
This book presents basic atomic theory as given in first and second year courses at university. It demonstrates that the structure of the Periodic Table as we know it is based on sound principles. Throughout the book, theoretical concepts are presented, along with the experimental evidence for them. Foundations are laid in the introductory chapter, which deals with fundamental particles, electromagnetic radiation and Heisenberg's uncertainty principle. Atomic orbitals are then described, using a minimum of mathematics, followed by a discussion of the electron configurations of the elements. Further chapters reveal the relationships between the electronic configurations of the elements and some properties of their atoms; and the variations in the properties of their fluorides and oxides across the periods and down the groups of the Periodic Table. Ideal for the needs of undergraduate chemistry students, Tutorial Chemistry Texts is a major new series consisting of short, single topic or modular texts concentrating on the fundamental areas of chemistry taught in undergraduate science courses. Each book provides a concise account of the basic principles underlying a given subject, embodying an independent-learning philosophy and including worked examples.